Application of failure mode and effect analysis (FMEA) and cause and effect analysis in conjunction with ISO2200 to a pistachio processing plant - Varzakas T.H.; Zakynthinos I.G.; Arvanitoyannis I.S. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
Failure Mode and Effect Analysis (FMEA) model has been applied for the risk assessment of pistacchio manufacturing. A tentative approach of FMEA application to the pistacchio industry was attempted in conjunction with ISO22000. Preliminary Hazard Analysis was used to analyse and predict the occurring failure modes in a food chain system (pistacchio processing plant), based on the functions, characteristics and/or interactions of the processes, upon which the system depends. Critical Control points have been identified and implemented in the cause and effect diagram (also known as Ishikawa, tree diagram and fishbone diagram). In this work comparison of ISO22000 analysis with HACCP is carried out over pistacchio processing and packaging. However, the main emphasis was put on the quantification of risk assessment by determining the Risk Priority Number (RPN) per identified processing hazard. Salting and roasting, hand grading of split nuts to remove defects and debris, packaging and storage or shipping, drying of split and non-split nuts to 5-7 percent moisture as well as dumping of nuts and conveying over an air leg to remove debris were the processes identified as the ones with the highest RPN (280, 240, 147, 144, 130, respectively) and corrective actions were undertaken. Following the application of corrective actions, a second calculation of RPN values was carried out leading to considerably lower values (below the upper acceptable limit of 130). It is noteworthy that the application of Ishikawa (Cause and Effect or Tree diagram) led to converging results thus corroborating the validity of conclusions derived from risk assessment and FMEA. Therefore, the incorporation of FMEA analysis within the ISO22000 system of a pistachio processing industry is considered imperative.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)